Tradisi VS Modernitas: Konflik Generasi dan Komunikasi Gender dalam Crashing Eid - Lilis Widarti; Rifma Ghulam Dzaljad; Yulia Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study investigates the intricate dynamics of tradition versus modernity through the lens of generational conflict and gender communication in the Netflix series